Accessing Queensland's soil information - an open data revolution!. (June 2015) - Bryant, Kelly; O'Brien, Lauren; Brough, Daniel
Abstract: The Queensland government is the custodian of soil and land resource information with an estimated value of 75 million. The Soil and Land Information (SALI) system houses this data from over 600 distinct studies with some 96, 000 soil observations dating back to the 1940s. This data is now not only used by government but by universities, councils, landowners, consultants and schools. Providing this information to the public in an easy and accessible way, with a focus towards online delivery is crucial. Previous issues with distribution of online soils information in Queensland have stemmed not only from limits to technology but also, changing departmental structures and multiple websites. The department which manages soils information in Queensland has undergone nine name changes in the last 12 years due to Machinery of Government (MoG) restructures. This constantly changing web presence and branding is as confusing for people sourcing soils information as it is for those providing it. The Queensland government has now moved to a whole of government online environment. This is a single website with no reference to the convoluted structures within government or department names. The aim is to prevent impacts from future MoG changes on the provision of data and information to the public. Queensland government soils now has a single dedicated website (qld.gov.au/environment/land/soil ) which has allowed us to start to build a repository for soils information and is a single portal for people to access soils data. It has been demonstrated that this consistent approach to websites improves trust and confidence of users [1] and from this, confidence in using Queensland soils information and data and ultimately better land management decisions.